The multi-objective optimization of a non-pneumatic wheel based on its life prediction. Issue 3 (25th March 2019) - Xiao, Zhen; Zhao, Youqun; Lin, Fen; Zhu, Mingmin; Deng, Yaoji; Zang, Liguo
Abstract : Purpose: A novel non-pneumatic safety tire, namely mechanical elastic wheel (ME-Wheel), has been developed recently to solve problems, including tire bursting and flat tire, of typical pneumatic tires. This paper aims to predict the life of the ME-Wheel accurately and settle the problem of lower lifespan. Design/methodology/approach: This study proposes a new method to establish a novel model of virtual proving ground based on finite element analysis, and by combining with the random vibration damage analysis method, the life of an ME-Wheel is predicted precisely. Next, the weak parts and infinite life parts of the ME-Wheel are investigated from the perspective of constant life design, and an approximate response surface model is developed, which is suitable for the ME-Wheel. Then, the optimal results of the ME-Wheel are obtained, including tire modal, mass and its lifetime. Findings: It is found that the proposed methods can provide a reliable theoretical basis for further improving the structural design and material selection of ME-Wheel parts. The results show that the improved ME-Wheel can reduce the weight and greatly improve the ability of anti-resonance, and the lifetime of ME-Wheel has significantly improved. Originality/value: A new type of non-pneumatic tire (ME-Wheel) has been developed to avoid problems with traditional tires, such as tire leaking or puncture. A new method to establish a novel model of virtual proving ground based on finite element analysis has been proposed. The weakest key component of the ME-Wheel is determined. The life, mass and modal of the ME-Wheel are optimized.